99. Multichannel video-EMG study of stiff person syndrome. Issue 1 (January 2015) - La Gioia, S.; Frigeni, B.; Venturelli, E.; Rottoli, M.R.; Foresti, C.
<x xml:space="preserve">Abstract</x> Stiff person syndrome (SPS) is a central nervous system disorder featured by muscular rigidity and trigger-induced spasms predominantly affecting proximal limbs and axial muscles. Impaired GABAergic inhibition is believed to be the underlying mechanism. Co-contraction of agonist–antagonists muscles and continuous firing of motor units (MU) at rest are the hallmarks of the disease. Unfortunately, routine electromyography (EMG) does not always supply definitive responses, nevertheless it becomes very useful to the diagnosis in mild clinical syndromes, especially in the absence of anti-glutamic acid decarboxylase antibodies. To describe the video-electromyographic (video-EMG) patterns of SPS. Two patients with a clinical suspicion of SPS were studied with simultaneous multichannel video-EMG recording in addition to routine EMG. Our two patients had different clinical onsets, duration and severity of disease. In both cases multichannel video-EMG allowed confirmation of the suspected diagnosis. The following features were recorded: (1) simultaneous and continuous firing of paravertebral MU at rest; (2) co-contraction of antagonists muscles (biceps–triceps); (3) disappearance of co-contraction after intravenous diazepam with concomitant recovery of strength in the previously hypertonic limb. Simultaneous multichannel video-EMG study provides an important complement to SPS diagnosis, which might become essential in ambiguous cases.